Impacts of life-events on sitting, TV viewing and computer use among women from disadvantaged neighbourhoods - Minakshi Nayak; Karen Wills; Megan Teychenne; Verity Cleland (BMC, 2022)
Abstract Background Little is known about how life events such as changes in parental or employment status influence sedentary behaviour (SB). Women from disadvantaged neighbourhoods are at particular risk of poor health, therefore, in this population group this study aimed to determine between changes in parental and employment status with sitting, television viewing (TV), and computer time. Methods Women (18-45 years) from socioeconomically disadvantaged neighbourhoods self-reported their employment status, number of children, sitting, TV, and computer time [(baseline (n = 4349), three (n = 1912) and 5 years (n = 1560)]. Linear (sitting) and negative binomial (TV and computer time) multilevel models adjusted for confounders were used to estimate the SB association with changes in life events. Results Compared to women who never had children during the study period, less sitting and computer time was observed for women when number of children remained unchanged, had their first child or additional child, and fewer children (< 18 years). Less TV was observed for women when number of children remained unchanged. Compared to women who remained employed full-time during the study period, sitting and computer time decreased among women when they decreased or increased their working hours or when remained employed part-time/not working. TV time increased among women when they decreased their working hours. Conclusion Among women, declines in SB were observed amongst those experiencing life events. Interventions to decrease SB may consider targeting women with no children, and future research should further explore how changes in employment type (e.g., non-manual to manual jobs) impact SB.